Analysis of Dynamic Properties of Accelerometer Using Fractional Derivatives - Miroslaw Luft; Daniel Pietruszczak; Elzbieta Szychta (Communications - Scientific letters of the University of Zilina, 2015)
The paper outlines the use of fractional derivatives for dynamic measurements while developing a method of improved description of dynamic properties of accelerometer, which the authors consider to be the original and unique achievement of their work. The main objective of the work is an implementation of a fractional calculus-based method which allows for a description of dynamic properties of signal processing of measuring transducers with fractional orders. A dynamics of transducer is identified by the ARX method (AutoRegressive with EXternal input identification method). Identification of accelerometer was accomplished with the use of the MATLAB&Simulink package.